The global epidemiology of Brucella infections in terrestrial wildlife: A meta‐analysis. Issue 2 (3rd August 2020) - Dadar, Maryam; Shahali, Youcef; Fakhri, Yadolah; Godfroid, Jacques
Abstract: Brucellosis is a widespread zoonotic disease with serious consequences on human and animal health. Brucella infections were reported in many terrestrial wild animals, from subtropical and temperate regions to arctic regions. In many areas, the epidemiology of brucellosis in wildlife is closely associated with the occurrence of the disease in livestock. Some wild species may contribute to the re‐introduction of Brucella infections in livestock (spillback), even in officially brucellosis‐free (OBF) regions. Through meta‐regression analysis, this study draws a global picture of the prevalence of Brucella spp. in terrestrial wild animals, trying to determine most affected subgroups as well as preferential sampling and screening methods. For this purpose, a literature search was carried out among publications published from 1983 to 2019. Different subgroups were compared according to animal species, feeding, gender, age as well as the method used for sampling and for brucellosis diagnostic. To determine heterogeneity of studies, chi‐squared test was used and a random‐effects model (REM) estimated the pooled prevalence among subgroups. A total of 68 publications, comprising 229 data reports/studies, were selected. The most‐reported Brucella species in wildlife was Brucella abortus, and the highest prevalence rate was found in American bison, Bison bison (39.9%) followed by Alpine ibex, Capra ibex (33%). Serology was the most widely applied diagnostic approach (66%), while PCR appeared to be highly sensitive (36.62% of positive results). The gender of animals showed no significant association with the prevalence of brucellosis ( p  > .05). Blood samples and visceral organs constituted the great majority of specimen used for the detection of Brucella spp., while lymph nodes showed a high prevalence of positive samples (94.6%). The present study provides insight into the global epidemiology and enzootic potential of brucellosis in wild terrestrial animals worldwide, aiming at helping the appropriate authorities to strengthen prevention, surveillance and control strategies.